O lezbičnem gledališču v Sloveniji - Šorli, Maja (Amfiteater (Ljubljana), 2017)
What is lesbian theatre? Does this category even exist in Slovenia? How to conceptualise and perform it? This article investigates the reach of lesbian theatre in both the wider sociological view - as a phenomenon in the Slovenian society - as well as in the narrower theatre studies field. It reviews the conditions (the origin of the LGBTIQ rights movement) and continues with the spaces in which lesbian theatre hides. It presents the Monospolno gledališče (Monosexual Theatre) and other examples of theatre practices: comedy, institutional performances, international festivals and marginal cases of lesbian contents. It also proposes a model of how to research lesbianism in the Slovenian theatre and guidelines for the future of lesbian theatre.
Keywords: homoseksualnost; homosexsuality; homosexuality; lesbian theatre; lesbians; lezbično gledališče; lezbijke; Monosexual theatre; Monospolno gledališče; sociologija gledališča; sociology of theatre